Mindfulness traits as potential inhibitor of irrational performance beliefs and intolerance of uncertainty amongst elite female basketball players - Koop, L.; Jooste, J. (Apunts Sports Medicine, 2023)
Dispositional mindfulness promotes adaptive responses to pressure situations and reduce anxiety and emotional distress, which are common manifestations in sport. The aim of this study was to investigate the role of mindfulness characteristics in the display of irrational performance beliefs and intolerance of uncertainty amongst a sample of elite female basketball players (N = 67, Mage = 25.73 years, SD = 4.4). An online Qualtrics survey containing demographic items, the Mindfulness Attention Awareness Scale, Irrational Performance Beliefs Inventory, and Intolerance of Uncertainty Scale was used to collect the study data, which were analysed using SPSS. The results from both Pearson correlation coefficient and simple linear regression analyses indicated that higher levels of dispositional mindfulness are significantly related to elite female basketball players having fewer irrational beliefs about their performance and being more tolerant of uncertain situations in their sport. One-way analysis of variance further indicated a significant difference between low, average, and high mindfulness groups, with Tukey's post-hoc analyses confirming that participants with high mindfulness displayed significantly fewer rigid, extreme, self-defeating performance beliefs in sport, and were less prone to impulsive reactions to uncertain circumstances compared to participants with low mindfulness. Sport psychology practitioners are encouraged to consider the integration of mindfulness assessment and training protocols with traditional cognitive behaviour modification approaches to counter female basketball players` display of distorted beliefs in sport and adverse reactions to ambiguous experiences.